Peningkatan Hasil Belajar Siswa Dengan Menggunakan Media Camtasia Studio - Waruwu, Nestapa Abadi; Silaban, Patri Janson; Sinaga, Reflina (Jurnal PGSD, 2020)
The results of this study shows that there was an increase in students’ learning outcomeson, the results of pre-test only 3 students 12% with learning outcomes mean score is 49. In the post-test cycle I increased to 10 students 38% with the learning outcomesmean score is 73. In the second cycle posttest, the completeness of learning outcomes increased to 23 students 88% with the learning outcomes mean score is 86. Furthermore, the result of observations of the teacher’s activities in carrying out learning in cycle I obtained an average of 68% and observations of the students’ activities obtained an average of 63. In cycle II the result of the teacher observations increased to 85% and the results of observations on the students’ activities also increased to 85. Thus the conclusion is obtained that by using the Camtasia Studio media there is an increase to the students’ learning outcome.